Даурия: роман / Константин Седых - Седых Константин Федорович (Сибириада, 2013)
Экземпляры: СБ (201503) / Инвентарный номер: 50783 / Цена: 226.10 / Сис.шифр: Р2 / Авт.знак: С 28 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6